Water Markets, Commodity Chains and the Value of Water - M., Marcus; Janakarajan, S. (Water Nepal, 2009)
Their paper situates debates over the functioning and role of water markets within the concept of management and adaptation. The paper argues that existing water markets in South Asia are fundamentally different from the formalised, legal, rights based water markets of Western United States. Keywords: water markets Water Nepal Vol. 12, No. 1&2, 2006 Page: 81-114